Pengaruh Customer Relationship Management (CRM) terhadap Loyalitas Pemustaka di Perpustakaan Universitas Andalas - Dinda Aprilya; Desriyeni Desriyeni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The purpose of this study is to describe: (1) Customer Relationship Management (CRM) at Andalas University Library; (2) user loyalty at Andalas University Library; (3) the effect of Customer Relationship Management (CRM) on user loyalty at Andalas University Library. This type of research is quantitative with a descriptive method. The population in this study were all visitors to Andalas University Library as of 2023, totaling 140,928 and a sample of 100 people. Sampling using simple random sampling technique. Data analysis was carried out through the stages of examination, tabulation, and drawing conclusions. The results of the study indicate that: (1) the implementation of Customer Relationship Management (CRM) at Andalas University Library has been implemented well, this can be seen from the responses given by respondents who stated that the completeness of technology-based services at Andalas University Library is relatively complete and makes it easier for users to get the books or references they need. In addition, the service process involving officers and users can be carried out quickly and accurately, in addition, the Andalas University library has also been supported by officers who are creative, responsive and able to serve the needs of users; (2) the level of loyalty of users who visit the Andalas University library is also relatively high, this can be seen from the existence of repeat purchases that occur repeatedly, in addition, users have a high level of retention, this can be seen from their actions to always want to visit the library almost every day, in addition, users are also concluded to have a high level of referrals, this can be seen from the number of respondents who choose to agree to invite friends to come and read books at the Andalas University Library; (3) according to the results of the hypothesis testing through the t-statistic test, it was found that Customer Relationship Management (CRM) has a positive and significant effect on user loyalty in visiting the Andalas University Library. These findings indicate that the better the implementation of Customer Relationship Management (CRM) felt by users, the more their loyalty will increase. The results obtained at the first hypothesis testing stage are in line with the proposed hypothesis, so the first hypothesis is accepted.